2016
DOI: 10.1016/j.cytogfr.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic regulation of cytokine receptor signaling

Abstract: Signaling of plasma membrane receptors can be regulated by endocytosis at different levels, including receptor internalization, endocytic sorting towards degradation or recycling, and using endosomes as mobile signaling platforms. Increasing number of reports underscore the importance of endocytic mechanisms for signaling of cytokine receptors. In this short review we present both consistent and conflicting data regarding endocytosis and its role in signaling of receptors from the tumor necrosis factor recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 153 publications
5
80
1
Order By: Relevance
“…In vivo , it is more likely that scavenging microglia encounter an infected astrocyte or neuron and become activated by signals released from these more permissive cell types. Activation of bystander microglia is strongly linked with neuroinflammation in a number of neurodegenerative diseases, and we hypothesized that it could significantly contribute to the pro-inflammatory cytokine load during VEEV infection [45,46]. Our investigation revealed that bystander microglia exposed to overlays from infected astrocytes produce significantly more IL-1α, IL-1β, IL-6, and IL-8 as compared to the directly infected cells.…”
Section: Discussionmentioning
confidence: 88%
“…In vivo , it is more likely that scavenging microglia encounter an infected astrocyte or neuron and become activated by signals released from these more permissive cell types. Activation of bystander microglia is strongly linked with neuroinflammation in a number of neurodegenerative diseases, and we hypothesized that it could significantly contribute to the pro-inflammatory cytokine load during VEEV infection [45,46]. Our investigation revealed that bystander microglia exposed to overlays from infected astrocytes produce significantly more IL-1α, IL-1β, IL-6, and IL-8 as compared to the directly infected cells.…”
Section: Discussionmentioning
confidence: 88%
“…Receptors are internalized from the plasma membrane into endocytic compartments, collectively called “endosomes” by endocytosis (8), which has long been recognized as a major mechanism to attenuate receptor signaling (14, 15). Constitutive (non-cytokine-induced) endocytosis regulates the number of receptors available on the cell surface to bind cytokines.…”
Section: Endocytosis and Signaling Of Cytokine Receptorsmentioning
confidence: 99%
“…Both CME and CIE are involved in endocytosis of cytokine receptors (15, 19, 3840). CME mediates endocytosis of gp130, the shared receptor for IL6 family cytokines, and receptors for prolactin, thrombopoietin, erythropoietin, interferon, IL5 (IL5Rα), IL7 (IL7Rα), and IL36 (18, 39, 4148).…”
Section: Endocytosis and Signaling Of Cytokine Receptorsmentioning
confidence: 99%
“…A common feature to all cytokine systems is that upon ligand stimulation cytokine-receptor complexes traffic to intracellular compartments, where they are often degraded, contributing to switching off the response (Becker et al, 2010;Bulut et al, 2011;Claudinon et al, 2007;German et al, 2011;Keeler et al, 2007;Shah et al, 2006). However, a complex positive regulatory role of endocytosis in cytokine signaling has emerged (Becker et al, 2010;Cendrowski et al, 2016;Fallon and Lauffenburger, 2000;Marchetti et al, 2006;Sarkar et al, 2002). Several studies recently suggested a novel role for the endosomal compartment in stabilizing cytokine receptor dimers by enhancing local receptor concentrations (Gandhi et al, 2014;Moraga et al, 2015a), thus contributing to signaling fitness even at low complex stabilities.…”
mentioning
confidence: 99%